2011
DOI: 10.1371/journal.pone.0016249
|View full text |Cite
|
Sign up to set email alerts
|

STK35L1 Associates with Nuclear Actin and Regulates Cell Cycle and Migration of Endothelial Cells

Abstract: BackgroundMigration and proliferation of vascular endothelial cells are essential for repair of injured endothelium and angiogenesis. Cyclins, cyclin-dependent kinases (CDKs), and cyclin-dependent kinase inhibitors play an important role in vascular tissue injury and wound healing. Previous studies suggest a link between the cell cycle and cell migration: cells present in the G1 phase have the highest potential to migrate. The molecular mechanism linking these two processes is not understood.Methodology/Princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 48 publications
1
36
0
1
Order By: Relevance
“…Further, we explored the roles of STK35 on the proliferation of osteosarcoma cells by knocking down its expression. It has been reported that STK35 could regulate cell cycle transition of endothelial cells [10]. Here, an in vitro CCK-8 assay and in vivo xenograft experiments demonstrated that down-regulation of STK35 expression remarkably suppressed the proliferation of osteosarcoma cell lines (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Further, we explored the roles of STK35 on the proliferation of osteosarcoma cells by knocking down its expression. It has been reported that STK35 could regulate cell cycle transition of endothelial cells [10]. Here, an in vitro CCK-8 assay and in vivo xenograft experiments demonstrated that down-regulation of STK35 expression remarkably suppressed the proliferation of osteosarcoma cell lines (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…A few studies have investigated the biological function of STK35. STK35 may regulate CDKN2A expression, G1- to S-phase transition and migration of endothelial cells [10]. Ectopic expression of STK35 enhanced caspase-independent cell death of cells undergoing oxidative stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…STK35, also known as CLIK1, STK35L1 and listed as one of the top potential targets for miR-377, contains complementary seed sequence in its 3′UTR that is highly conserved among human, chimpanzee, mouse, rat, guinea pig, rabbit, dog, cow, elephant, and horse (Figure 6A). Unlike other cytoplasmic kinases, STK35 is a novel kinase, mainly localized in the nucleus and nucleolus, that binds to nuclear actin (15); thus, it might play a critical role in directly modulating gene transcription machinery (16). A previous study showed that VEGF-stimulation in endothelial cells up-regulates STK35 expression and that STK35 knockdown leads to diminished angiogenic ability of endothelial cells (15).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, VEGF stimulates STK35 expression in endothelial cells (15). A well-known proangiogenic cytokine, VEGF promotes EPC migration, differentiation, and angiogenic function.…”
Section: Discussionmentioning
confidence: 99%
“…47 STK35 encodes a serine/threonine protein kinase linking the cell cycle and migration of endothelial cells. 48 While additional studies are warranted to elucidate the biological mechanisms of these genes, these data support the opinion that gene-based approaches may play a key role in identifying novel genetic mechanisms that could be missed by relying on single-marker methods of analysis. 37,49 …”
Section: Discussionmentioning
confidence: 58%